2018
DOI: 10.1029/2017wr021324
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Measurements to Determine the Hydrologic Partitioning of Snowmelt on a Snow‐Dominated Subalpine Hillslope

Abstract: In subalpine watersheds of the intermountain western United States, snowpack melt is the dominant water input to the hydrologic system. The primary focus of this work is to understand the partitioning of water from the snowpack during the snowmelt period and through the remainder of the growing season. We conducted a time‐lapse electrical resistivity tomography (ERT) study in conjunction with a water budget analysis to track water from the snow‐on through snow‐off season (May–August 2015). Seismic velocities p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 79 publications
4
53
0
Order By: Relevance
“…Previous studies demonstrated that when only one state variable (water content in this study) is changing, interpretations of relative changes from time‐lapse resistivity observations are less impacted by uncertainty in the relationship between inverted resistivity and water contents (Cassiani et al, ; Thayer et al, ). The borehole NMR data in this study provide quantitative details about the volumetric changes of water in the subsurface but at a much smaller scale.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Previous studies demonstrated that when only one state variable (water content in this study) is changing, interpretations of relative changes from time‐lapse resistivity observations are less impacted by uncertainty in the relationship between inverted resistivity and water contents (Cassiani et al, ; Thayer et al, ). The borehole NMR data in this study provide quantitative details about the volumetric changes of water in the subsurface but at a much smaller scale.…”
Section: Discussionmentioning
confidence: 61%
“…To compare results from both methods with each other, sections of the resistivity profile around Wells 1 and 2 were directly compared with borehole NMR measurements in these wells just before irrigation and just after flooding has ceased (Figure ). The resistivity values were converted to volumetric water content values based on an Archie's type relationship (Archie, ) from lab measurements that is used to convert from resistivity to water content (Moreno et al, ; Thayer et al, ). The conductivity of the water used in the lab was 381 μS/cm, which was similar to the 389‐μS/cm conductivity of the irrigation water.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrical resistivity tomography (ERT), which measures the spatial distribution of subsurface resistivity, has emerged as a useful geophysical tool for studying the subsurface and tracking hydrologic processes. Due to the general tendency of decreasing resistivity with increasing water content, ERT has commonly been used in a time-lapse capacity to monitor infiltration processes at the event scale (Batlle-Aguilar et al, 2009;Dietrich, Weinzettel, & Varni, 2014;Michot et al, 2003) and seasonal moisture fluctuations (French & Binley, 2004;Jayawickreme, Van Dam, & Hyndman, 2008;Kotikian, Parsekian, Paige, & Carey, 2018;Schwartz, Schreiber, & Yan, 2008;Thayer et al, 2018). Other geophysical tools such as seismic refraction and ground-penetrating radar (GPR) can provide valuable information regarding subsurface structure (Holbrook et al, 2014;McClymont, Hayashi, Bentley, & Liard, 2012;Mills, 1990;Neal, 2004;Parsekian, Singha, Minsley, Holbrook, & Slater, 2015).…”
Section: Introductionmentioning
confidence: 99%